Two new species of Impatiens (Balsaminaceae) from Putao, Kachin State, northern Myanmar - Yang, Bin; Zhou, Shi-Shun; Maung, Kyaw Win; Tan, Yun-Hong (Phytotaxa, 2017)
Two new species of the genus Impatiens (Balsaminaceae) from Putao, Kachin State, Myanmar, are here described and illustrated. Impatiens casseabriae can be easily recognized by its narrowly elliptic to narrowly oblanceolate leaves, petioles up to 3 mm long, lower lateral united petals 25–40 mm long. Impatiens putaoensis differs from its closely related species I. xanthina in having light greenish yellow flowers, lateral sepals ovate to elliptic, lower lobe of united petals semilunar, upper lobe of united petals dolabrate, dorsal petal ovate to nearly orbicular, with a narrow inconspicuous dorsal crest. Molecular phylogenetic analyses of sequences from both nuclear ribosomal and plastidgenes confirm that the two new species are distinct from previously recorded species.